Dragonhead Cyclone in The Falkland Islands (Malvines Islands) has Double Cote's Spiral Like NGC 5247 - Ricardo, Gobato; Abhijt, Mitra; Sana, Ahmed (Journal of Weather Changes, 2024)
Extratropical cyclones are common in the South Atlantic. They generally arise with the passage of cold fronts to the south of the South American continent, crossing the south of Chile and Argentina, in the regions of Puerto Natales, Punta Arenas (Chile), Rio Galegos, Rio Grande, El Calafate and Ushuaia (Argentina). The extratropical cyclone analyzed presented at its peak the very characteristic shape of a Chinese dragon. Other cyclones in the form of a Cote's spiral curve are part of this analysis (Gobato et al., 2018-2023).  They present a mathematical form of a double Cotes Spiral curve. Here called the Dragonhead cyclone, indicate a structural similarity with spiral galaxies, especially NGC 5247, in the constellation Virgo. With an area of influence and a size of around 3,247 thousand km2 at its peak, it moved quickly in a west-northwest (WNW) direction, with an average speed of 76 km/h, with winds of 84 km/h at 100 km from the nucleus, as it passed north of the Falkland Islands (Malvinas Islands). The cyclone temperature during its trajectory varies from -45ºC to -50ºC at its edge, while at its core it varies between -10ºC to -25ºC. In the data collected (Gobato et al., 2018-2023), and analyzed from the Dragonhead cyclone, it is clear that all extratropical cyclones that appear south of the South American continent, below 40° latitude, have the shape of a spiral curve, like the spiral galaxy. Most of these are in the form of a double Cote’s spiral curve.
Keywords: Cyclones; South American; Spiral Galaxy; NGC 5247; South Atlantic; Chinese dragon